Pengaruh profitability, firm age, growth opportunities, dan business risk terhadap DER perusahaan sektor consumer cyclicals di BEI tahun 2021-2023 - Amalia Rissa Mufida; RA Sista Paramita (Universitas Negeri Surabaya, 2025)
This study aims to examine and analyze in depth the effect of profitability, firm age, growth opportunities, and business risk on the Debt to Equity Ratio (DER) as an indicator of a company’s capital structure. The research population includes all companies operating in the consumer cyclicals sector listed on the Indonesia Stock Exchange during the 2021–2023 period. Through the purposive sampling method, a total of 44 companies that met the research criteria were selected as the sample. Data analysis was conducted using panel data regression with the aid of Stata version 17 software to obtain accurate and reliable results. The findings reveal that profitability, firm age, and business risk have no significant effect on DER. In contrast, the growth opportunities variable has a positive and significant influence on DER. Based on these findings, it is recommended that companies focus more on enhancing growth opportunities, as increased sales and business expansion may lead to optimal adjustments between debt and equity composition.